Uma análise de implicatura convencional em redações do ENEM - Lopes, Ludmila Dias do Nascimento Serafim (2021)
In a literate society, the production of the dissertative-argumentative text is an activity frequently requested by different institutions, mainly in schools and in exams such as entrance exams and Enem. Thus, considering the Enem, the production of the essay genre requires the observance of criteria related, mainly, to the structure and organization of the textual type of dissertative-argumentative and the use of linguistic mechanisms necessary for the construction of the argumentation. Thus, to mobilize their arguments and express their ideas, the participant needs to structure his text in order to fulfill the competencies required in the Exam. For this, in addition to structural and compositional aspects, the compliance with Textualization Criteria advocated by Textual Linguistics as well as the mobilization of argumentative strategies are essential for the writing of the genre. Among these strategies, in this work, we highlight the inferences. In this perspective, the Gricean concept of Conventional Implicatures that there are linguistic items that convey specific meanings is relevant to be analyzed in the constitution of the Enem essay genre. One point in particular is the use of expressions of an opinion character, with an argumentative weight, therefore, that can contribute to the characterization of the argumentative-argumentative text, which motivated us to investigate how Cis, as a particular type of inferences, appear in texts such as Enem. Based on this perspective, this paper analyzes the occurrence of Conventional Implicatures with an argumentative burden in Enem’s essays. For this, as theoretical support, we take Liberato and Fulgêncio (2010) and Wolf (2019) ‘s view of inferences, as a process involved in a comprehensive and effective writing / reading, the textualization criteria in Marcuschi (2008), the Gricean theory on implicatures (1975/1982) as well as the study by Oliveira and Basso (2014) on this topic, in addition to expanding the Gricean concept from Bach (1999) and Potts (2005). As a corpus we used some essays that make up the Cartilha Redação a Mil: 30 redações do Enem 2018, compiled by candidates who achieved the highest score in Enem, and we propose a quantitative and qualitative analysis. The results indicate that Cis contribute to direct the argumentative path and intensify the persuasive force of the text; and further reveal that the textualization criteria are directly related to the study on this type of inference.